The lost symbol - Brown, Dan (Doubleday New York, 2009)
Symbologist Robert Langdon, summoned to Washington, D.C. by his mentor, finds himself plunged into a clandestine world of Masonic secrets, hidden history, and secret locations--all of which seem to be dragging him toward a single, inconceivable truth